The scenario of knowledge, attitude and practice of the Bangladeshi population towards thalassemia prevention: A nationwide study - Nur E. Alam; Md Shariful Islam; Md Imam Ul Khabir; Umme Suriea; Md Muzahidul Islam; Ramisa Binti Mohiuddin; Sumaiya Akter; Nahid Mahamud; Md Nazmul Islam Bappy; Dipankar Sardar; Shahin Mahmud; Kamal Chowdhury; et al. (Public Library of Science (PLoS), 2022)
Thalassemia is one of the most common life-threatening yet preventable congenital hemoglobin disorders especially in South Asian regions like Bangladesh. It has become a rising public health concern for Bangladesh as 6-12% of the population are carriers and many of them are unaware of it. The purpose of the study is to inspect the knowledge and attitude towards thalassemia among the general people of Bangladesh. A cross-sectional survey was conducted in eight administrative regions of Bangladesh between January and October of 2020. A structured questionnaire was designed to collect information about thalassemia and socio-demographic characteristics. Multivariate logistic regression models were used to identify factors associated with knowledge of thalassemia. A p-value <0.05 was considered significant. Of the 1,248 participants, only 47.4% had heard of thalassemia. Half of the participants who heard about the disease had no idea that thalassemia was not a transfusion transmitted disease. Only 49.8% of participant correctly identified consanguineous marriages as an important risk factor. Majority of them knew that marriage between two carriers can lead to a child with thalassemia major. About 72.5% knew that blood tests are a diagnosis method to determine thalassemia. Among the socio-demographic variables, the level of education of the respondents was identified as an independent predictor for knowledge (p<0.05) on thalassemia. For example, graduate (aOR: 24.88; 95% CI: 6.238-99.232) or post-graduate (aOR: 33.18; 95% CI: 7.864-140.001) participants were more aware of thalassemia than non-graduates. However, about 68.2% of the participants showed a positive attitude towards premarital screening of themselves or their family members and 85.3% were willing to donate blood to thalassemia patients. The study shows that there is a need to disseminate the information on thalassemia since the knowledge gap is huge among people. These findings will strengthen the implementation of thalassemia major awareness through educational programs, health counseling, premarital screening and campaigning.